De re i de dicto - Cieśluk, Andrzej (Diametros, 2009)
The aim of the article is to systematize the de re/de dicto distinctions that are most frequently used in philosophy. The paper highlights the main contexts in which these distinctions may be found and their syntactic, semantic, and pragmatic definitions. The article consists of four points, which are discussed in turn: 1) the principal moments in the early history of the distinction between de re and de dicto; 2) the main theoretical contexts of this distinction; 3) contemporary attempts to systematize the various versions of this distinction, derived from Thomas McKay and Michael Nelson; and 4) a similar attempt, conducted by the author, to make McKay and Nelson’s systematization more precise.